Presenting a Model for Robot evaluation and Ranking by Grey MuLTIMOORA - Ahmadreza Ghasemi; Meysam Shahbazi; Hamidreza Aghashahi (مدیریت مهندسی و رایانش نرم)
Regarding Proliferation of Robot brands and models and contributing criteria in evaluation of them, using a powerful model to Robots evaluation and ranking is very important. This research try to find key contributing factor in Robots evaluation and present an efficient model to Robot selection. To achieve mentioned goal, in the first step main robot performance criteria identified by experts. In addition 5 popular Robot in Irankhodro automotive industry were identified. Next criteria weights were calculated by Grey Entropy method. Sellers training, quality of services, are the main important criteria’s and v.s precision and degree of freedom are least important criteria. In addition by synthesizing three Grey MOORA approaches, KOKA, ABB, Motoman, Fanuc and Hyundai are the result ranking.